Outcomes of acute kidney injury in children at Muhammad Husin Hospital, Palembang - Hertanti lndah Lestari; Dahler Bahrun; Eka lntan Fitriana (Paediatrica Indonesiana, 2014)
Background Acute kidney injury (AKI) is a common problemin hospitalized pediatric patients, with effects on morbidity andmortality.Objectives To assess for the incidence and common etiologies ofAKI, as well as to review factors that affect patient outcomes atMuhammad Husin Hospital, Palembang.Methods We reviewed data from our nephrology registry fromJanuary 2010 to June 2013. Independent variables were age, stageand etiology of AKI, requirement of renal replacement therapy(RRT) , and PICU admission. The dependent variable was patientoutcomes, categorized as survived or died. Association betweenclinical data and outcomes were analyzed by Chi-square test.Results The incidence of AKI was 28.3%. Using the pediatric risk,injury, failure, loss, end stage renal disease (pRIFLE) criteria, 65(36.7%) patients were in the risk stage, 56 (31.6%) in the injurystage, and 56 (31.6%) in the failure stage. Twelve (6.8%) patientsrequired RRT and 29 (16.4%) patients were admitted to the PIW.The mortality rate from AKI was 20.9%. The common etiologies ofAKI were acute glomerulonephritis (55 subjects; 31.1 % ), multipleorgan dysfunction (24 subjects; 13.6%), dehydration (23 subjects;13.0%), hypoalbuminemia (20 subjects; 11.3%), heart failure (11subjects; 6.2%) and nephrotoxic agents (12 subjects; 6.8%) . Themortality rate was significantly higher in children of younger age(<5 years) (P=0.0001), in the failure stage of AKI (P=0.014),with non-renal origin of illness (P=0.0001) and those with anindication for PIW admission (P=0.0001).Conclusion AKI is found in one-third of nephrology patients.The most common etiology of AKI is acute glomerulonephritis.One-fifth of patients with AKI do not survive. Recognition ofriskfactors and detection of AKI in early stages might improve patientoutcomes.